Blockchain for Supply Chain Resilience, Transparency, and Trust: a Multi-Case Study Analisys - Borodacheva, Nataliya (My University, 2025)
Due to increasing complexity and vulnerability of supply chains to disruptions, many companies explore the potential of blockchain technology to improve transparency, resilience and trust. This study explores how blockchain supports these goals through qualitative approach with multi-case studies from agri-food, shipping and logistics, retail, and automobile industries – Terra Delyssa, Maersk, Walmart and Volvo. Based on SCRM (Supply Chain Risk Management) Theory and Trust Theory, the research combines secondary data with insights from two expert interviews to provide a comprehensive overview of blockchain value and its adoption challenges. Thematic analysis was used to analyze the data, and guided by four key themes: enhancing traceability and transparency, risk reduction and supply chain resilience, building consumer and stakeholder trust, and challenges in blockchain adoption. The findings illustrate that blockchain can strengthen resilience, enhance transparency, and mitigate risks. However, its successful implementation more likely depends on stakeholder alignment, governance models, digital maturity, and integration with existing systems. In some contexts, the dominance of centralized systems limits blockchain’s transformative potential. From a managerial perspective, the study emphasizes the importance of aligning blockchain efforts with real business needs and stakeholder readiness, investing in digital skills, and ensuring strong data governance. This thesis contributes to the existing literature by providing a cross case-study analysis on blockchain’s role in supply chain management and highlights the key limitations and barriers to its successful and sustainable implementation.
Keywords: fi=Tuotantotalous (kauppatieteet)|en=Industrial Management|; Master's Programme in Industrial Management